Pengembangan Media Berbasis Android Berbantuan Aplikasi iSpring Suite pada Pembelajaran Matematika untuk Siswa Kelas V SD - Ovi Larassaty (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2022)
This study aims to determined the development, feasibility, and user responses of Android-based media assisted by iSpring Suite. The development method used is 4D but only limited through three stages, namely define, design, and develop. Research data obtained through documentation, questionnaires, and interviews. The results of the research was Android-based media assisted by iSrping Suite on valid volume material based on expert assessments on three aspects of feasibility. Feasibility of the material with a validity of 0.90, the feasibility of language with a validity of 0.90, and the feasibility of a graphic with a validity of 0.87. User responses during the limited trial to 98% of students respons, and 99% of teachers' responses. These results indicated that Android-based media assisted by iSpring Suite are feasible and got a very good response.